Načeli sorazmernosti in pro rata temporis - Novak, Janez (Podjetje in delo, 2014)
The article discusses the proportionality principle often applied in the case law of Slovenian Constitutional Court, as well as in the case law of the European Court of Justice and European Court of Human Rights. The views and findings of some other courts (e.g. German Federal Labour Court - Bundesarbeitsgericht) regarding this principle are also important. The principle of proportionality means that in deciding on the scope of encroachment upon a certain right one has to judge on its suitability for achieving a specific goal, on its necessity and whether used criterion burdens person concerned excessively. The substance of the principle, unessential variations of it aside, is accepted by all aforementioned courts and is one of the fundamental criteria in their adjudication. The case law of Slovenian courts demonstrates that the principle of proportionality is under-used and not taken into consideration as often as it should be. Judging from available source, one could conclude that the principle of pro rata temporis is virtually unknown in Slovenian case law and jurisprudence. The essence of the principle is that the scope of a certain right (e.g. length of annual leave) is recognized in relation to temporary execution of a certain right or duty (e.g. depending on the length of working hours or employment) relative to a comparable full-time employee. The material is covered in four sections: the concept, legal regulation, case law, and peculiarities in labour disputes.
Keywords: pravice; sodišča; sodna praksa; sorazmernost